Inhibition of neutrophil activation by alpha1-acid glycoprotein. - Costello, M J (1984)
We report that alpha1-acid glycoprotein (AAG), a naturally occurring human plasma protein and acute phase reactant of uncertain biological function, inhibits human neutrophil aggregation and superoxide anion generation induced by a variety of stimuli including zymosan treated serum, formyl-methionyl-leucyl-phenylalanine and phorbol myristate acetate. Inhibition was transient, directly proportional to the glycoprotein concentration and inversely proportional to the concentration of the stimulus added. Desialyzation, resulting in the removal of a substantial portion of the molecule's negative charge, did not alter the effectiveness of AAG. Removal of the penultimate galactose residues from desialyzed AAG resulted in a slight but significant reversal of inhibition, suggesting that the heteropolysaccharide units of AAG may be important for inhibition of cellular function. We therefore suggest that the acute phase glycoprotein AAG may be a significant modulator of neutrophil as well as platelet and lymphocyte function during inflammation.